Correlation Assessment of the Effect of Macronutrient Deficiency on The Organism of Children - Choliyeva Muhayyo Azam kizi (Genius Journals, 2022)
Today, due to the lack of protein, carbohydrates and fats in food, the additional demand for macro and micronutrients among people is increasing. In particular, physical development is adversely affected as a result of inadequate intake of macronutrients. The spread of these indicators among age groups was found to be significantly lacking in macronutrients in young children among the population. As a result of our research, it was found that even in the group of 5-year-old children of preschool age, the need for proteins, carbohydrates and fats is not fully covered. The lack of macronutrients in the food is the reason for the reduction of the corresponding substances in the blood.
Keywords: Macronutrient; bromcresol method; protein; carbohydrate